# Functions of Random Variables

Dec 8, 2019
Mar 11, 2022 15:59 UTC
Finding the distribution of a real-valued function of multiple random variables. There's the method of distribution functions, transformations and moment generating functions.

Suppose we have random variables $X_1, \cdots, X_n$, and a real-valued function $U(X_1, \cdots, X_n)$. In this chapter, we’re only going to do one thing: introduce multiple methods to find the probability distribution of $U$. Any one of these methods can be employed to find the distribution , but usually one of the methods leads to a simpler derivation than the others. The “best” method varies from one application to another.

## The method of distribution functions

The first way of finding the distribution of $U$ is using the definition directly.

$$F_U(a) = P\{U \leq a\} = P\{ U(X_1, \cdots, X_n) \leq a \}$$ We can work this out in the following steps:

1. Write out the distribution function of $U$:

$$F_U(a) = P\{ U(X_1, \cdots, X_n) \leq a \}$$

1. Find the region of $X_1, \cdots, X_n$ such that $U(X_1, \cdots, X_n) \leq a$ and denote the region as $D$.

2. Integrate $f(X_1, \cdots, X_n)$ over $D$.

$$F_U(a) = \int\int\limits_D \cdots \int f(x_1, \cdots, x_n)dx_1 \cdots dx_n$$

The hardest part of this method is finding the set $D$. We’ll gain some insight with some examples.

### Sugar example

A company is selling sugar online. Suppose the amount of sugar it can sell per day is $Y$ tons, which is a continuous random variable with density function defined as

$$f_Y(y) = \begin{cases} 2y, & 0 \leq y \leq 1 \\ 0, & \text{otherwise} \end{cases}$$

For each ton of sugar sold, the company can earn $\$300$. The daily operation cost is$\$100$. Find the probability distribution of the daily income of this company.

Solution: Let the random variable $X$ denote the daily profit in hundred dollars. We want to write $X$ as $g(Y)$ and find $F_X(a)$.

\begin{aligned} X &= 3Y - 1 \\ F_X(a) &= P\{X \leq a\} \\ &= P\{ 3Y - 1 \leq a \} \\ D &= \{Y: 3Y - 1 \leq a\} \\ &= \left\{Y \leq \frac{a+1}{3}\right\} \\ F_X(a) &= \int\limits_{Y \leq \frac{a+1}{3}}f_Y(y)dy \\ &= \int_{-\infty}^\frac{a+1}{3} f_Y(y)dy \end{aligned}

If $\frac{a+1}{3} < 0$, $f_Y(y) = 0$ $\Rightarrow$ $F_X(a) = 0$. If $\frac{a+1}{3} > 1$, $f_Y(y) = 1$ $\Rightarrow$ $F_X(a) = 1$. When $0 \leq \frac{a+1}{3} \leq 1$,

\begin{aligned} F_X(a) &= \int_0^\frac{a+1}{3} f_Y(y)dy \\ &= \int_0^\frac{a+1}{3} 2ydy \\ &= y^2 \bigg|_0^\frac{a+1}{3} \\ &= \frac{(a+1)^2}{9} \end{aligned}

Note that as $y$ ranges from $0$ to $1$, $u$ ranges from $-1$ to $2$, so the distribution function of $X$ is

$$F_X(a) = \begin{cases} 0, & a < -1 \\ \frac{(a+1)^2}{9}, & -1 \leq a \leq 2 \\ 1, & a > 2 \end{cases}$$ The density function can also be calculated:

$$f_X(x) = \frac{dF_X(a)}{da} = \begin{cases} 0, & a < -1 \text{ or } a > 2 \\ \frac{2}{9}(a+1), & -1 \leq a \leq 2 \end{cases}$$

### Example of two variables

Suppose $Y_1$ and $Y_2$ are two continuous random variables with joint density function

$$f(y_1, y_2) = \begin{cases} 3y_1, & 0 \leq y_2 \leq y_1 \leq 1 \\ 0, & \text{otherwise} \end{cases}$$ Find the density function of $U = Y_1 - Y_2$. Also use the density function of $U$ to find $E[U]$.

We first need to find $F_U(a)$ and use it to obtain the density function $f_U(u)$.

$$F_U(a) = P\{U \leq a\} = P\{Y_1 - Y_2 \leq a\}$$

Now we need to find the region of $y_1$ and $y_2$. We know that $y_1 - y_2 \leq a$ and $0 \leq y_2 \leq y_1 \leq 1$, and $a$ is bounded between $0$ and $1$ due to the latter condition. The area shaded in red and not in blue is the region of $y_1$ and $y_2$.

We can find the integral by subtracting the lower-right blue triangle region ($P\{U \geq a\}$) from the entire red triangle1.

$$\begin{gather*} D = \{y_1, y_2: 0 \leq y_1 \leq 1, 0 \leq y_2 \leq y_1\} \\ F = \{y_1, y_2: a \leq y_1 \leq 1, 0 \leq y_2 \leq y_1 - a \} \end{gather*}$$

\begin{aligned} F_U(a) &= \iint_D f(y_1, y_2)dy_1dy_2 - \iint_F f(y_1, y_2)dy_1dy_2 \\ &= 1 - \int_a^1 \int_0^{y_1 - a} f(y_1, y_2)dy_2 dy_1 \\ &= 1 - \int_a^1 dy_1 \int_0^{y_1 - a}3y_1 dy_2 \\ &= 1- \int_a^1 3y_1(y_1 - a) dy_1 \\ &= 1 - \left( y_1^3 - \frac{3}{2}ay_1^2 \right)\bigg|_a^1 \\ &= 1 - \left( 1 - \frac{3}{2}a - a^3 + \frac{3}{2}a^3 \right) \\ &= \frac{a}{2}\left(3-a^2\right),\quad 0 \leq a \leq 1 \end{aligned}

So the distribution function of $U$ is

$$F_U(a) = \begin{cases} 0, & a < 0 \\ \frac{a}{2}\left(3-a^2\right), & 0 \leq a \leq 1 \\ 1, & a > 1 \end{cases}$$

Calculating the density function of $U$ is now straightforward:

\begin{aligned} f_U(a) &= \frac{dF_U(a)}{da} = \frac{d\left[ \frac{3}{2}a - \frac{1}{2}a^3 \right]}{da} \\ &= \frac{3}{2} - \frac{3}{2}a^2 \\ &= \frac{3}{2}(1-a^2), \quad 0 \leq a \leq 1 \end{aligned}

which gives us

$$f_U(u) = \begin{cases} \frac{3}{2}\left(1-u^2\right), & 0 \leq u \leq 1 \\ 0, & \text{otherwise} \end{cases}$$

The expectation of $U$ can be calculated as

\begin{aligned} E[U] &= \int_0^1 u \cdot \frac{3}{2}(1-u^2)du \\ &= \int_0^1 \frac{3}{2}(u - u^3)du \\ &= \frac{3}{2}\left[ \frac{u^2}{2} - \frac{u^4}{4} \right] \bigg|_0^1 \\ &= \frac{3}{2} \cdot \frac{1}{4} = \frac{3}{8} \end{aligned}

## Sum of independent random variables

An important application of the method of distribution functions is to calculate the distribution of $Z = X + Y$ from the distributions of $X$ and $Y$ when they are independent, continuous random variables.

The first few steps are the same as what’s described above:

$$F_{X+Y}(a) = P\{X+Y \leq a\} = \iint\limits_{X+Y \leq a} f_{X,Y}(x, y)dxdy$$

Define the region $D$ such that

$$D = \{x, y: -\infty < y < \infty, -\infty < x < a-y \}$$

We have

\begin{aligned} F_{X+Y}(a) &= \iint\limits_D f_{X, Y}(x, y)dxdy \\ &= \int_{-\infty}^\infty \int_{-\infty}^{a-y}f(x, y)dxdy \end{aligned}

Now the independence comes into place:

\begin{aligned} F_{X+Y}(a) &= \int_{-\infty}^\infty f_Y(y)dy \underbrace{\int_{-\infty}^{a-y}f_X(x)dx}{P\{X \leq a-Y\}} \\ &= \int{-\infty}^\infty F_X(a-y)f_Y(y)dy \end{aligned}

The distribution function of $F_{X+Y}(a)$ is called the convolution of $F_X(a)$ and $F_Y(a)$. By differentiating the above distribution function, we can find the density function of $X+Y$.

\begin{aligned} f_{X+Y}(a) &= \frac{d}{da}\left\{ \int_{-\infty}^\infty F_X(a-y)f_Y(y)dy \right\} \\ &= \int_{-\infty}^\infty \frac{d}{da}F_X(a-y)f_Y(y)dy \\ &= \int_{-\infty}^\infty f_Y(y)dy \left[ \frac{d}{da}F_X(a-y) \right] \\ &= \int_{-\infty}^\infty f_Y(y)dy \left[ \frac{dF_X(a-y)}{d(a-y)}\frac{d(a-y)}{da} \right] \\ &= \int_{-\infty}^\infty f_Y(y) f_X(a-y)dy \end{aligned}

### Uniform distribution example

If $X$ and $Y$ are two independent random variables both uniformly distributed on $(0, 1)$, calculate the probability density of $X+Y$. We can directly apply the equation above:

$$\begin{gather*} f_{X+Y}(a) = \int_{-\infty}^\infty f_Y(y)f_X(a-y)dy \\ f_Y(y) = f_X(x) = \begin{cases} 1, & 0 \leq x \leq 1 \text{ or } 0 \leq y \leq 1 \\ 0, & \text{otherwise} \end{cases} \\ f_{X+Y}(a) = \int_0^1 1 \cdot f_X(a-y)dy \end{gather*}$$

We know that $0 \leq y \leq 1$ and $0 \leq a-y \leq 1$. There are several cases here:

1. If $a \leq 0$, $a-y \leq 0$, then $f_X(a-y) = 0$.
2. If $0 < a \leq 1$, we also need $a-y \geq 0$, or $0 \leq y \leq a$.
3. If $1 < a \leq 2$, we also need $a-y \leq 1$, or $y \geq a-1$.
4. If $a > 2$, $f_X(a-y) = 0$.

When $0 \leq a \leq 1$,

$$f_{X+Y}(a) = \int_0^a f_X(a-y)dy = \int_0^ady = a$$

When $1 \leq a \leq 2$,

$$f_{X+Y}(a) = \int_{a-1}^1 f_X(a-y)dy = 2-a$$

In summary,

$$f_{X+Y}(a) = \begin{cases} a, & 0 < a \leq 1 \\ 2-a, & 1 < a \leq 2 \\ 0, & \text{otherwise} \end{cases}$$

The sum of two uniform random variables is called a triangular random variable because of the shape of the density function above2.

### Normal distribution example

Suppose $X$ and $Y$ are two independent standard normal random variables. Find the density of $Z = X + Y$. Recall that

$$f_X(x) = \frac{1}{\sqrt{2\pi}} e^{-\frac{x^2}{2}}, f_Y(y) = \frac{1}{\sqrt{2\pi}} e^{-\frac{y^2}{2}}$$

\begin{aligned} f_{X+Y}(a) &= \int_{-\infty}^\infty f_X(a-y)f_Y(y)dy \\ f_X(a-y)f_Y(y) &= \frac{1}{2\pi}e^{-\frac{(a-y)^2}{2} - \frac{y^2}{2}} \\ &= \frac{1}{2\pi} \exp\left\{ -\frac{a^2 - 2ay + 2y^2}{2} \right\} \\ &= \frac{1}{2\pi} \exp\left\{ -\frac{4y^2 - 4ay + 2a^2}{4} \right\} \\ &= \frac{1}{2\pi} \exp\left\{ -\frac{(2y-a)^2 + a^2}{4} \right\} \\ &= \underbrace{\frac{1}{2\pi} \exp\left\{ -\frac{a^2}{4} \right\}}{\text{constant w.r.t. }y} \exp\left\{ -\frac{(2y-a)^2}{4} \right\} \\ f{X+Y}(a) &= \frac{1}{2\pi}\exp\left\{-\frac{a^2}{4}\right\} \int_{-\infty}^\infty \exp\left\{ -\frac{(2y-a)^2}{4} \right\}dy \\ &= C \cdot \exp\left\{-\frac{a^2}{4}\right\} \end{aligned}

Therefore $X+Y$ is a normal random variable with mean 0 and variance 2. Similar results of this example can be obtained for a more general case, which is a very important property of normal random variables.

#### Theorem

Let $X_i$, $i = 1, \cdots, n$ be a sequence of independent normal random variables with parameters $\mu_i$ and $\sigma_i^2$, then $\sum_{i=1}^n X_i$ is normally distributed with parameters $\sum_{i=1}^n \mu_i$ and $\sum_{i=1}^n \sigma_i^2$.

$$\sum_{i=1}^n X_i \sim N\left( \sum_{i=1}^n \mu_i, \sum_{i=1}^n \sigma_i^2 \right)$$

## The method of transformations

We first consider the univariate case. Suppose $X$ is a continuous random variable with density function $f_X(x)$. To find

$$Y = g(X) \Rightarrow F_Y(a)$$

what we can do is to transform the condition back to a condition of $X$. We know that $g^{-1}(x)$ exists when the function $g(\cdot)$ is monotonic, i.e. $\forall x_1 \neq x_2$, $g(x_1) \neq g(x_2)$.

Given $g(x)$ is a monotonic function of $X$, $g(\cdot)$ maps every distinct value of $X$ to a distinct value of $y$.

If $g(\cdot)$ is a monotonically increasing function,

$$\begin{gather*} F_Y(a) = P\{g(X) \leq a\} = P\left\{ X \leq g^{-1}(a) \right\} = F_X\left( g^{-1}(a) \right) \\ f_Y(a) = \frac{dF_Y(a)}{da} = \frac{dF_X(g^{-1}(a))}{dg^{-1}(a)} \cdot \frac{dg^{-1}(a)}{da} = f_X(g^{-1}(a))\frac{dg^{-1}(a)}{da} \end{gather*}$$

If $g(\cdot)$ is a monotonically decreasing function,

$$\begin{gather*} F_Y(a) = P\{g(X) \leq a\} = P\left\{ X \geq g^{-1}(a) \right\} = 1- F_X\left( g^{-1}(a) \right) \\ f_Y(a) = \frac{d[1-F_X(g^{-1}(a))]}{da} -\frac{dF_Y(a)}{da} = f_X(g^{-1}(a))\left[-\frac{dg^{-1}(a)}{da}\right]\end{gather*}$$

These two cases can be unified as follows using the difference in the sign of $\frac{dg^{-1}(a)}{da}$. If $g(X)$ is a monotonic function for all $x$ such that $f_X(x) > 0$,

$$f_Y(a) = f_X\left( g^{-1}(a) \right) \left| \frac{dg^{-1}(a)}{da} \right|$$

### Sugar example revisited

In the sugar example, we defined the density function of $Y$ as

$$f_Y(y) = \begin{cases} 2y, & 0 \leq y \leq 1 \\ 0, & \text{otherwise} \end{cases}$$

and $U = g(Y) = 3Y-1$. Find $f_U(u)$ with the method of transformations.

When $y_1 < y_2$,

$$g(y_1) - g(y_2) = 3(y_1 - y_2) < 0$$

so $g(\cdot)$ is a monotonically decreasing function. The inverse function is

$$Y = g^{-1}(U) = \frac{U+1}{3}$$

and the first derivative is

$$\frac{dg^{-1}(u)}{du} = \frac{d\frac{u+1}{3}}{du} = \frac{1}{3}$$

Now we can find the density function using the formula

\begin{aligned} f_U(u) &= f_Y(g^{-1}(u)) \left| \frac{dg^{-1}(u)}{du} \right| \\ &= f_Y\left( \frac{u+1}{3} \right) \cdot \frac{1}{3} \\ &= 2\left(\frac{u+1}{3}\right) \cdot \frac{1}{3}, \quad 0 \leq \frac{u+1}{3} \leq 1 \end{aligned}

Clean this up a bit and we get

$$f_U(u) = \begin{cases} \frac{2}{9}(u+1), & -1 \leq u \leq 2 \\ 0, & \text{otherwise} \end{cases}$$

### Multivariate example

The transformation method can also be used in multivariate situations. Let random variables $Y_1$ and $Y_2$ have a joint density function

$$f(y_1, y_2) = \begin{cases} e^{-(y_1 + y_2)}, & y_1 \geq 0, y_2 \geq 0 \\ 0, & \text{otherwise} \end{cases}$$

Find the density function for $U = Y_1 + Y_2$.

We can prove that $Y_1 \perp Y_2$ and use the method described earlier to find the distribution for the sum of two independent random variables. We can also apply the method of transformations here. If we fix $Y_1 = y_1$, we have

$$U = g(Y_1, Y_2) = y_1 + Y_2 = h(Y_2)$$

From here we can consider this as a one-dimensional transformation problem.

\begin{aligned} Y_2 &= U - y_1 = h^{-1}(u) \\ f_{Y_1, U}(y_1, u) &= f_{Y_1, Y_2}\left[y_1, h^{-1}(u) \right] \left| \frac{dg^{-1}(u)}{du} \right| \\ &= e^{-(y_1 + u - y_1)} \cdot 1 \\ &= e^{-u}, \quad y_1 \geq 0, \quad y_2 = u - y_1 \geq 0 \end{aligned} Which is

$$f_{U, Y_1}(u, y_1) = \begin{cases} e^{-u}, & 0 \leq y_1 \leq u \\ 0, & \text{otherwise} \end{cases}$$

Using the joint density function of $Y_1$ and $U$, we can obtain the marginal density function of $U$:

\begin{aligned} f_U(u) &= \int_{-\infty}^\infty f_{U, Y_1}(u, y_1)dy_1 \\ &= \int_0^u e^{-u}dy_1 \\ &= ue^{-u}, \quad u \geq 0 \end{aligned}

$$f_U(u) = \begin{cases} ue^{-u}, & u \geq 0 \\ 0, & \text{otherwise} \end{cases}$$

### Multivariate procedure

As shown in the example above, when our problem is $U = g(X_1, X_2)$ and we want to find $f_U(u)$, the procedure is

1. Fix $X_1 = x_1$, and denote

$$U|_{X_1 = x_1} = h(X_2) = g(X_1 = x_1, X_2)$$

1. Calculate the joint density function of $X_1$ and $U$ using the formula

$$f_{X_1, U}(x_1, u) = f_{X_1, X_2}\big(x_1, h^{-1}(u) \big)\left| \frac{dh^{-1}(u)}{du} \right|$$

1. Find the marginal density of $U$ with

$$f_U(u) = \int_{-\infty}^\infty f_{X_1, U}(x_1, u)dx_1$$

Suppose random variables $Y_1$ and $Y_2$ have a joint density function

$$f(y_1, y_2) = \begin{cases} 2(1-y_1), & 0 \leq y_1 \leq 1, 0 \leq y_2 \leq 1 \\ 0, & \text{otherwise} \end{cases}$$

Find the density function of $U = Y_1Y_2$.

Following the procedure, we first fix $Y_1 = y_1$ for some $0 \leq y_1 \leq 1$. Then we consider the univariate transformation $U = h(Y_2) = y_1Y_2$ and get the joint density function for $Y_1$ and $U$.

\begin{aligned} U|{Y_1 = y_1} &= g(Y_1 = y_1, Y_2) = y_1Y_2 = h(Y_2) \\ Y_2 &= h^{-1}(U) = \frac{u}{y_1}, \frac{dh^{-1}(u)}{du} = \frac{1}{y_1} \\ f{Y_1, U}(y_1, u) &= f_{Y_1, Y_2}(y_1, h^{-1}(u))\left| \frac{dh^{-1}(u)}{du} \right| \\ &= 2(1-y_1) \cdot \frac{1}{y_1}, \quad 0 < y_1 \leq 1, \quad 0 \leq y_2 = \frac{u}{y_1} \leq 1 \end{aligned}

The joint density function of $Y_1$ and $U$ is

$$f_{Y_1, U} = \begin{cases} \frac{2}{y_1}(1-y_1), & 0 < y_1 \leq 1, 0 \leq u \leq y_1 \\ 0, & \text{otherwise} \end{cases}$$

and now we can obtain the marginal density of $U$:

\begin{aligned} f_U(u) &= \int_{-\infty}^\infty f_{Y_1, U}(y_1, u)dy_1 \\ &= \int_u^1 \frac{2}{y_1}(1-y_1) dy_1 \\ &= 2\int_u^1 \left( \frac{1}{y_1} - 1 \right)dy_1 \\ &= 2[\ln(y_1) - y_1]\bigg|_u^1 \\ &= 2[(0 - 1) - (\ln(u) - u)] \\ &= 2[u - \ln(u) - 1], \quad 0 \leq u \leq 1 \end{aligned}

## The method of moment generating functions

We know that for a random variable $X$, its associated moment generating functions $M_X(t)$ is given by $E\left[e^{tX}\right]$. The $k^{th}$ moment can help us find $E[X^k] = M_X^{(k)}(0)$.

For random variables $X$ and $Y$, if both moment generating functions exist and $M_X(t) = M_Y(t)$, we have $F_X(a) = F_Y(a)$, i.e. $X$ and $Y$ have the same probability distribution.

### Normal random variables

Let $Z \sim N(0, 1)$ and $X = \sigma Z + \mu$. Show that $X \sim N(\mu, \sigma^2)$ using the method of moment generating functions.

Define $Y \sim N(\mu, \sigma^2)$. If we can show that $M_X(t) = M_Y(t)$, then the distribution of $X$ is identical to the distribution of $Y$.

\begin{aligned} M_Y(t) &= E\left[ e^{tY} \right] = \int_{-\infty}^\infty e^{ty}f_Y(y)dy \\ &= \exp\left\{ \frac{\sigma^2 t^2}{2} + \mu t \right\} \\ M_X(t) &= E\left[ e^{tX} \right] = E\left[ e^{t(\sigma Z + \mu)} \right] \\ &= E\left[ e^{t\mu}e^{(t\sigma)Z} \right] \\ &= e^{t\mu} E\left[ e^{(t\sigma)Z} \right] \\ &= e^{t\mu} M_Z(t\sigma) \end{aligned}

We know that $M_Z(t) = \exp\left\{ \frac{t^2}{2} \right\}$, so

\begin{aligned} M_X(t) &= e^{t\mu} e^{\frac{\sigma^2t^2}{2}} \\ &= \exp\left\{ \frac{\sigma^2t^2}{2} + \mu t \right\} = M_Y(t) \end{aligned}

### Use for sum of independent random variables

The method of moment generating functions is also very useful for calculating the probability distributions for the sum of independent random variables.

Suppose $X$ and $Y$ are independent with moment generating functions $M_X(t)$ and $M_Y(t)$. If $U = X + Y$, then

\begin{aligned} M_U(t) &= E\left[e^{tU}\right] = E\left[e^{t(X+Y)}\right] \\ &= E\left[\underbrace{e^{tX}}_{g(X)} \cdot \underbrace{e^{tY}}_{h(Y)}\right] \\ &= E\left[e^{tX}\right]E\left[e^{tY}\right] = M_X(t) \cdot M_Y(t) \end{aligned}

In this special case,

$$X \perp Y \Leftrightarrow M_{X+Y}(t) = M_X(t) M_Y(t)$$

### Some more examples

Find the distribution of $X+Y$ if $X$ and $Y$ are

1. independent binomial random variables with parameters $(n, p)$ and $(m, p)$, respectively.
2. independent Poisson random variables with parameters $\lambda_1$ and $\lambda_2$, respectively.

In the first scenario we have $X \sim Bin(n, p)$ and $Y \sim Bin(m, p)$. $M_{X+Y}(t) = M_X(t)M_Y(t)$ since $X \perp Y$. Recall that

$$M_X(t) = \left(pe^t + 1 - p \right)^n$$

so the MGF of $X+Y$ is

$$M_{X+Y}(t) = \left(pe^t + 1 - p \right)^{m+n}$$

which tells us $X+Y \sim Bin(m+n, p)$.

In the second case, we have $X \sim Pois(\lambda_1)$ and $Y \sim Pois(\lambda_2)$. Since

$$M_X(t) = \exp\left\{ \lambda(e^t - 1) \right\}$$

the MGF of $X+Y$ can be written as

\begin{aligned} M_{X+Y}(t) &= \exp\{\lambda_1(e^t-1)\} \cdot \exp\{\lambda_2(e^t-1)\} \\ &= \exp\{(\lambda_1 + \lambda_2)(e^t-1)\} \end{aligned} So $X+Y \sim Pois(\lambda_1 + \lambda_2)$.

1.   1 2 3 4 5 6 7 8 9 10 11 12 13  library(ggplot2) ggplot(NULL, aes(x = c(0, 1))) + stat_function( fun = ~ .x - 0.3, geom = "area", xlim = c(0.3, 1), fill = "#0073C2", alpha = 0.7 ) + stat_function( fun = ~ .x, geom = "area", xlim = c(0, 1), fill = "#CD534C", alpha = 0.5 ) + geom_segment(aes(x = 1, y = 0, xend = 1, yend = 1), linetype = "dashed") + geom_segment(aes(x = 0, y = 1, xend = 1, yend = 1), linetype = "dashed") + labs(x = expression(y), y = expression(y)) + ggpubr::theme_pubr() 
↩︎
2.  1 2 3 4 5 6 7  ggplot(NULL, aes(x = c(-1, 3))) + stat_function(fun = ~ 0, geom = "line", xlim = c(-1, 0)) + stat_function(fun = ~ .x, geom = "line", xlim = c(0, 1)) + stat_function(fun = ~ 2 - .x, geom = "line", xlim = c(1, 2)) + stat_function(fun = ~ 0, geom = "line", xlim = c(2, 3)) + labs(x = "a", y = expression(f[X+Y](a))) + ggpubr::theme_pubr() 
↩︎

Related Posts
 Dec 28 Sampling Distribution and Limit Theorems 6 min read Nov 06 Multivariate Probability Distributions 23 min read Nov 01 Common Continuous Random Variables 17 min read Oct 06 Common Discrete Random Variables 14 min read Oct 06 Definitions for Discrete Random Variables 7 min read